Representation of Identity and Politics in the Song "Ojo Dibandingke" at the 77th Indonesian Independence Day State Ceremony at the State Palace - Yulaeliah, Ela; Saepudin, Asep; Sukotjo, Sukotjo; Cuenza, Yves P; Ulhage, Ahza Al Amal (Resital: Jurnal Seni Pertunjukan, 2025)
The purpose of this research is to analyze the representation of identity and political image in the song "Ojo Dibandingke" during the 77th Indonesian Independence Day commemoration in 2022 at the State Palace. The song "Ojo Dibandingke" is a popular dangdut koplo song from 2022. The song was created by Abah Lala, an artist from Banyuwangi. Hall's (1977) representation theory, particularly the constructionist approach and the encoding–decoding model, is used to read how the meaning of the lyrics is produced by the creator (encoding) and interpreted by the users (decoding). A qualitative method with a case study approach was conducted to gather data through webography, documentation, literature review, interviews, and observation. Several interesting points regarding the presentation of the song "Ojo Dibandingke" include: the song "Ojo Dibandingke" is sung by a child who is still underage, dangdut koplo music is not typically performed at state events, and there are altered lyrics that praise the president's name. This research indicates that the use of the song "Ojo Dibandingke" in the 77th Independence Day celebration at the State Palace was not merely an aesthetic choice, but a cultural representation practice laden with political and symbolic meaning. The presence of this song was not just an aesthetic presentation, but an arena for negotiating cultural and political identity in public space.